A COISA JULGADA NA SENTENÇA TERMINATIVA NO CÓDIGO DE PROCESSO CIVIL DE 2015 (Reflection and Critique Law Magazine, 2022)
The concept of ruling has been constantly changed in our legislation. With the advent of the Code of Civil Procedure 2015 there was a new modification, indicating that it is not enough only the content of the judicial act to be based on the hypotheses of Article 485 and 487, but also to end the common procedure or extinguish the execution.Aside from the concept of judgment, the legislature decided to broaden the positive regarding the identification of situations in which the procedural ruling will not prevent the rediscussion of the matter of merit in another case, provided that the procedural defect is properly remedied.However, there are hypotheses in which it is not possible to correct the defects that underpinned the final ruling, and the debate arises about the possibility of these procedural judgments being covered by the material thing, and no longer by the thing judged formal, or if there would be another kind of yoke thing, more specific to these situations.This brief addresses the concept of ruling and thing judged to later identify the differences about the different species thing judged - the material and formal - and, in the end, conclude whether there was a change in which thing judged covered the thing judged when the delivery of the procedural rulling based on the hypotheses of Article 485, I, IV, VI and VII.